High-cycle fatigue behavior of austenitic steel and pure copper under uniaxial, proportional and non-proportional loading - Pejkowski, Łukasz (Strojniški vestnik, 2014)
Austenitic steel EN: X2CrNiMo17-12-2 (ASTM: 316L) and copper Cu-ETP (DIN: E-Cu58, EN: CW004A, ASTM: C11000) were subjected to tension-compression, torsion and complex loads, including non-proportional loads. The non-proportionality of the state of stress resulted from a phase shift of the value delta = 90° of load components with sine signals and variable ratio of shear to normal stress lambda. On the basis of the results, Wöhler's curves were prepared, presenting the dependency of fatigue life to equivalent stress levels. Their analysis shows that fatigue life is strictly connected with the value of coefficient lambda. The existence of its critical value can also be observed, which results in the highest fatigue life reduction. The value is different for each material. Furthermore, fractographic tests were conducted showing the influence of the level and type of load on the fracture face.
Keywords: fraktografija; neproporcionalna obremenitev; večosno utrujanje; visokociklično utrujanje; zunaj faze